MANAJEMEN KEPALA SEKOLAH DALAM MENGEMBANGKAN SARANA PRASARANA PENDIDIKAN DI SMP COKRO AMINOTO MUARADUA OKU SELATAN - Lisman,; Subhan, (UNISAN JURNAL, 2024)
The School Principal's management plays a vital role in developing educational facilities and infrastructure at SMP Cokro Aminoto Muaradua Oku Selatan in Enggal District, City. The purpose of this study is to explore the role of the School Principal in developing educational facilities and infrastructure at SMP Cokro Aminoto Muaradua Oku Selatan in Enggal District, City, and to evaluate the effectiveness of efforts made by the School Principal in improving educational facilities and infrastructure. This study used a qualitative method with data collection techniques through in-depth interviews and observation. Research participants included the School Principal, teachers, and administrative staff at SMP Cokro Aminoto Muaradua Oku Selatan in Enggal District, City. The results of the study showed that the School Principal plays a crucial role in developing educational facilities and infrastructure at SMP Cokro Aminoto Muaradua Oku Selatan in Enggal District, City. The School Principal makes efforts such as proposing projects, collaborating with relevant parties, and monitoring the progress of these projects. Additionally, the School Principal motivates and involves all members of the school in actively developing educational facilities and infrastructure. Keywords : Management, Educational Facilities and Infrastructure